Review of Hadith Criticism on the Phenomenon of Aurat in Generation Z’s Dance Content on Social Media - Zahro, Fatimatus; Syarifah, Hasnia Imroatis (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2025)
The dance challenge phenomenon on social media platforms such as TikTok has become a popular trend among Generation Z, while also raising moral and spiritual issues concerning the boundaries of entertainment from an Islamic perspective. Many young people perceive entertainment as a form of freedom of expression without considering the values of manners (adab) and ethics taught by the Prophet Muhammad. This study aims to examine the meaning of hadiths on entertainment and pleasure in Islam, describe the dance challenge phenomenon and the behavior of Generation Z on social media, analyze such behavior from the perspective of hadith, and explore the relevance of prophetic teachings to the challenges of contemporary digital life. Using a library research method with a qualitative descriptive approach, data were collected from thematic hadiths, classical and contemporary Islamic literature, as well as recent studies on the digital behavior of young people. The findings reveal that entertainment in Islam is not absolutely prohibited but should remain within the limits of moderation (wasathiyah) and the principles of sharia. The hadiths emphasize the importance of balance between physical and spiritual needs and warn against entertainment that involves immorality (ma‘siat), tabarruj, or digital ostentation (riya’). The dance challenge can be positive when directed toward creative and educational expression but becomes negative when it violates Islamic moral norms. Therefore, the hadith serves as an ethical guideline for young Muslims to enjoy digital entertainment in a healthy, refined, and spiritually meaningful way.